2010
DOI: 10.1152/ajpgi.00510.2009
|View full text |Cite
|
Sign up to set email alerts
|

Ephrin B2/EphB4 pathway in hepatic stellate cells stimulates Erk-dependent VEGF production and sinusoidal endothelial cell recruitment

Abstract: Chemotaxis signals between hepatic stellate cells (HSC) and sinusoidal endothelial cells (SEC) maintain hepatic vascular homeostasis and integrity and also regulate changes in sinusoidal structure in response to liver injury. Our prior studies have demonstrated that the bidirectional chemotactic signaling molecules EphrinB2 and EphB4 are expressed in HSC. The aim of our present study was to explore whether and how the EphrinB2/EphB4 system in HSC could promote SEC recruitment, which is essential for sinusoidal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 40 publications
1
45
0
1
Order By: Relevance
“…5300). These cells have been well characterized and used widely in prior publications (10,32,46). Wild-type mouse embryonic fibroblast (MEF) cells, MEF cells isolated form c-abl and Arg doubleknockout mice (c-abl Ϫ/Ϫ MEF), and MEF cells isolated from Yes, Src, and Fyn knockout mice (YSF Ϫ/Ϫ MEF) were kindly provided by Drs.…”
Section: Methodsmentioning
confidence: 99%
“…5300). These cells have been well characterized and used widely in prior publications (10,32,46). Wild-type mouse embryonic fibroblast (MEF) cells, MEF cells isolated form c-abl and Arg doubleknockout mice (c-abl Ϫ/Ϫ MEF), and MEF cells isolated from Yes, Src, and Fyn knockout mice (YSF Ϫ/Ϫ MEF) were kindly provided by Drs.…”
Section: Methodsmentioning
confidence: 99%
“…Das et al 43 indicated that stimulation of human hepatic stellate cells with either ephrinB2 Fc or EphB4 Fc significantly increases VEGF mRNA levels, whereas small interfering RNAs for ephrinB2 and EphB4 inhibit this increase. They further observed that ephrinB2 stimulates phosphorylation of extracellular signalregulated kinases, which are key cell survival and proliferation proteins, to regulate VEGF-A expression through HIF-1 phosphorylation.…”
Section: Figmentioning
confidence: 99%
“…These findings indicate that VEGF might play a critical role in tissue angiogenesis under hypoxia as it does normally, but the lack of corresponding secretion of ephrinB2 protein will influence permanent angiogenesis of implanted tissues under hypoxia. 43 Therefore, we should focus on strategies that increase the protein expression of ephrinB2 in SCAP under hypoxia, and further explore the correlation between VEGF and ephrinB2 expression.…”
Section: Figmentioning
confidence: 99%
“…Prior research has described the role of Ephrin-B2 and EphB4 in delineating arterial and venous boundaries in developing tissue. Their expression has been implicated in mediating angiogenesis and hepatic vascular structure formation during cirrhosis [19][20][21][22][23]. This may be an interesting avenue of future research for extremity vascular malformations.…”
Section: Check For Updatesmentioning
confidence: 97%